Welcome to Royal Prep - Marsoli, Lisa Ann, 1958-; Character Building Studio; Disney Storybook Artists (New York : Disney Press, 2013)
"It's Open House at Royal Prep! Will Sofia and her friends get everything ready in time?"--P. [4] of cover.
Keywords: Princesses -- Fiction; Preparatory schools -- Fiction